MANTIK TARİHİNDEN BİR SAYFA: YAHYA B. ADÎ (893/4-974) - Ahmet Kayacık (İslami İlimler Dergisi)
Yahya Ibn Adi has an important role in translation movement from Greek to Arabic or Syriac in Tenth century. He also worked for contiuantion of this movement. This study contens, the short story of life him, his Works, especially in logic; and his activities in different fields of knowledge. The reader can find also some knowledges about his place or role in logical studies and his school and his being a chain in medico-logical tradition for next generations and finally for Andalus.